The chemistry of mucin glycoprotein in swiftlet (Aerodramus fuciphagus) edible bird's nest - Shim, Eric Kian Shiun (2019)
The chemistry of mucin glycoprotein in edible bird’s nest (EBN), an esteemed delicacy and broad-spectrum supplement, produced by swiftlet Aerodramus fuciphagus has been explored in this thesis.